Effect of the fluid flow fragmentation on the hydrothermal performance enhancement of a serpentine mini-channel heat sink. (April 2021) - Jaffal, Hayder Mohammad; Freegah, Basim; Hussain, Ammar A.; Hasan, Ala
Abstract: This paper aims to investigate the effect of fluid flow fragmentation on the hydrothermal performance characteristics of a serpentine mini-channel heat sink (SMCHS) numerically and experimentally. Two novel designs, namely, perpendicular and diagonal, which are related to where the fluid flow is fragmented in the SMCHS, are investigated. The two new designs have two entrances and two exits. The flow in each entrance is divided into two branches. In the current study, 3D CFD ANSYSIS–Fluent program is used in the numerical simulations. The three designs, namely, one conventional and the two novel designs, were manufactured and tested to validate the reliability of the numerical simulations and to compare the performance experimentally. The analysis of the results shows that the flow fragmentation effectively improves the SMCHS characteristics compared with the conventional SMCHS. Moreover, the outcomes indicate that the improved heat transfer of the fragmentation disperser, represented by the Nusselt number, increases by 13% accompanied by a reduction in the pressure drop by about 180% compared with the conventional design. The new SMCHS with the perpendicular fragmentation design is found to be slightly better than that with the diagonal fragmentation design. Highlights: Novel design of SMCHS is proposed based on flow fragmentation. Flow fragmentation plays a vital role in the reduction of pressure drop through SMCHS. Hydrothermal performance of SMCHS is significantly improved using flow fragmentation. SMCHS with orthogonal segmentation showed better overall performance than that with diagonal segmentation. The overall performance of the SMCHS with segmentation increases with increasing the cooling water mass flow rate.